Factors Influencing Capital Structure in Property and Real Estate Sector Companies Listed on IDX 2021-2023 - Lisnawati, Lisnawati; Permatasari, Fatimah; Budianto, Erwin (University of Darussalam Gontor, 2025)
This study examines the influence of profitability, asset structure, and firm size on firms' capital structure in the property and real estate industry listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023. The research utilizes a quantitative approach, integrating secondary data from corporate financial statements and the IDX website. The sampling strategy is a purposive sampling method, picking 16 companies from a total population of 93. Data analysis is performed using multiple regression analysis with SPSS version 25. The findings demonstrate that profitability and asset composition substantially negatively influence capital structure, implying that firms with more profitability and asset holdings are inclined to utilize less debt financing. Nonetheless, business size does not exhibit a substantial impact on capital structure. Nonetheless, when examined concurrently, profitability, asset structure, and firm size impact capital structure decisions.